HOW ARE THE INTENTIONS AND PERCEPTIONS OF SMES ON THE USE OF DIGITAL PAYMENTS USING QRIS IN THE CITY OF KEDIRI - Ria Lestari Pangastuti; Krissantina Efery; Nonni Yap (Jurnal Ekonomi, 2023)
This research is a study of the intentions and perceptions of msme actors towards the use of digital payments using qris in the city of kediri. This research is a qualitative type with 20 msme actors as respondents. With the first result being the perception of benefits, it turns out that the perceived benefits are balanced, 10 actors can already feel it and 10 others have not because they are new to digital payments with qris. Perceptions of convenience according to msme actors who were respondents stated that qris was very easy to use in all transactions. Meanwhile, from the perception of risk so far felt by the respondents there is no risk that is too fatal when using qris as a digital payment tool. From this it can be concluded that the large benefits, convenience and small risks make msme actors who are very familiar with qris prefer to use qris in every transaction intensively.